(untitled) (Journal of Partial Differential Equations, 1990)
ln this paper we are devoted to the free boundary problem u_t = &#916A(u) (x,t) &#8712 G_r,r u(x, 0) = &#966(x) &#8712 G_0 u|_r = 0 (&#8706A(u)&#8706x_iv_i + &#968(x)v_1)|_r = 0, where A’(u) &#8805 0. Under suitable assumptions we obtain the existence and uniqueness of global radial solutions for n =2 and local radial solutions for n &#8805 3.